ANALISIS ISI KOMENTAR NETIZEN PADA IKLAN SHAMPOO REJOICE 3IN1 X KIKI SAPUTRI #RAMBUTNODRAMA (The Commercium, 2023)
This research discusses the response of netizens to the Rejoice3in1 version of Kiky Saputri in the YouTube ad "#RambutNoDrama". The ad, which is wrapped in elements of humor and the selection of comedian brand ambassador Kiky Saputri, is the first woman to break the stigma for Rejoice Indonesia. This is because it is dif erent from Rejoice Indonesia's previous advertising habits, which oftenuse brand ambassadors and campaign concepts through advertisements that tendto be aimed at hijab-wearing women and even non-comedians. The author in this study uses the theory of content analysis, advertising, brand ambassadors, representation theory and message reception by categorizing positive, neutral, negative comments inaccordance with S-O-R theory and Public Sphere Theory and using the Holsti formula as a Reliability Test. This study aims to determineth ad impressions. This research approach is quantitative. The population and sample in this study were 826 comments. The results of this study from 826 comments obtained the highest frequency in the positive comment category, with 714 comments and a percentage of 86.44%, the second highest category was the neutral category with 58 comments and a percentage of 7.2%, and the lowest response was in the negative category with 54 comments and a percentage of 6.53%. In the positive category comments based on the Holsti formula, show a very strong, reliable and reliable level. This shows that the audience's attraction to the latest Rejoice advertising concept provides a suficient positive response and is dominated by comments approving and accepting the messages in the advertisements that are aired. This is categorized by the author that the hypothesis of this study can be accepted